Os estágios de desenvolvimento e as representações semióticas no contexto do processo ensino-aprendizagem na matemática - Cardoso, Marleide Coan (2003)
The objective of this study is to verify the possible existent relations among intelectual development stages and the semiotic representation, in the teaching and learning Mathmatics processes, connected to the study of the function. The sample used was the specific study. The students from first serie of Dehon High School – Tubarão – SC were responsible by the research. A sequence of activities were instruments which they utilized. The activities were shared in six groups in a mathmatic class during the school year of 2002. The activities were organized according to the contents studied by the students during that period. The revision of literature is, mainly, based on studies connected to the stages of development through the Piaget’s and Peirce’ s theories, and the relations in the teaching and learning mathmatics processes according to the context. Through the theories and analyses of the activities made by the students, some conclusions discussed around the context were specified and connected to the goal of this study and people involved in the research.